Enhancing Credit Card Product Management Through Machine Learning Insights and Predictive Analytics - Abraaz Mohammed Khaja (International Journal of Intelligent Systems and Applications in Engineering, 2022)
In the cutthroat credit card sector, efficient product management is essential and necessitates a thorough comprehension of consumer preferences, industry trends, and operational difficulties. The use of predictive analytics and machine learning (ML) to improve credit card product management is examined in this study. Institutions can create products that are suited to a variety of user categories by utilizing sophisticated machine learning algorithms to examine spending habits, client transaction patterns, and demographic information. The study shows how predictive analytics helps make well-informed decisions about things like interest rate optimization, reward structuring, and client retention tactics. Furthermore, proactive risk management and the detection of new market opportunities are made possible using machine learning insights. The success of these strategies in enhancing competitive advantage, customer satisfaction, and operational efficiency is confirmed by case studies and experimental studies. The results demonstrate the revolutionary potential of data-driven approaches to credit card lifecycle management and product creation.